Ziauddin Sardar: Membangun Epistemologi Islam - Ihsan, M. Taufik (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2023)
The lag behind Muslims from the West led to the emergence of the idea of the Islamization of science, which was initiated by one of them, al-Faruqi. However, this idea received criticism from Ziauddin Sardar. This criticism gave rise to the idea of "Building Epistemology". Therefore, this paper aims to discuss this idea. The problems in this paper are studied using a Literature Review approach. The literature used comes from journal articles that are relevant to the study of the ideas of Building Islamic Epistemology put forward by Ziauddin Sardar. Based on the discussion, it can be concluded that what al-Faruqi offered through efforts to instill Islamic values into science which is formed by western paradigms, concepts, ideologies and perceptions is wrong and has more potential to cause the Westernization of Islam than Islamization.